EKSPEKTASI ONGKOS GARANSI DUA DIMENSI MENGGUNAKAN KEBIJAKAN NON- RENEWING KOMBINASI FRW DAN PRW - , IRMA YUNIAR PANGESTI RAHAYU, Dr. Danardono MPH. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Warranty is a bond that is given to products that require companies to assign compensation to consumers if the product fails to function normally after the purchase of usage during the specified warranty period. Offering warranty will generate expense which is called warranty cost. Therefore, estimation of warranty cost is very important to be done. This paper will studying two dimentional warranty that is limited by time and usage, with non-renewing free replacement warranty policy for non- repairable product. Calculation of expected warranty costs using a two-dimensional joint distribution of variable distribution and usage time, in example bivariate distribution. Modeling of failure to follow the bivariate Pareto distribution, with parameters obtained through MLE method. In calculating the expected cost of warranty policies FRW, used type of convolution integral and Laplace transform that use software to get the solution, as well as in the calculation of the expected refund policy PRW.